Efficient removal of organophosphate esters by ligand functionalized MIL-101 (Fe): Modulated adsorption and DFT calculations. (September 2022) - Fan, Sheng; Lu, Xinru; Li, Haoliang; Du, Xiaodong; Huang, Xiaoyu; Ma, Yao; Wang, Juan; Tao, Xueqin; Dang, Zhi; Lu, Guining
Abstract: Organophosphate esters (OPEs) are a new class of flame retardants present in diverse waters. The study focused on the removal of aqueous OPEs using functionalized MIL-101(Fe), which was a representative of the metal-organic frameworks (MOFs). Adsorption kinetics of tris(2-chloroethyl) phosphate (TCEP), tributyl phosphate (TnBP), and triphenyl phosphate (TPhP) were investigated. Additionally, TCEP was selected as the model contaminant to study the adsorption isotherms, thermodynamics, and effect of solution matrix properties. Adsorption mechanisms obtained from the experiments were confirmed using density functional theory (DFT) calculations. Adsorption kinetics indicated that functionalized MOFs provided a significant enhancement to the removal of TCEP. The maximum adsorption capacities q m of MIL-101(Fe), MIL-101(Fe)–NH2, MIL-101(Fe)–OH, and MIL-101(Fe)–CH3 at 298 K for TCEP were 76.040, 282.940, 119.680, and 181.274 μmol/g, respectively. By comparing the adsorption behavior of functionalized MOFs, MIL-101(Fe)–NH2 was proved to be most efficient for TCEP removal. Based on the adsorption experiments and DFT calculations, TCEP removal was dominated by physical adsorption. The van der Waals (vdW) interactions and hydrogen bonding were assumed to be involved in the adsorption. This work proves that appropriate ligand functionalization is promising for the removal of aqueous OPEs, which also provides a new insight for the control of OPEs pollution. Graphical abstract: Image 1 Highlights: Four MIL-101(Fe) MOFs were synthesized with ligand functionalization. MIL-101(Fe)–NH2 exhibited efficient adsorption abilities towards TCEP. Different OPEs involved different adsorption mechanisms. Functional groups can provide additional adsorption sites.